Constraints Facing Teachers of Christian Religious Education in Using Life Approach in Secondary Schools in Nairobi East District in Kenya - Amukowa, Wyclife O.; Ngunju, Alice W. (MCSER-CEMAS-Sapienza University of Rome, 2013)
The strategy used in teaching and learning has a bearing on effectiveness and quality of education offered. The integrated Christian Religious Education (CRE) lays emphasis on what is known as the life Approach strategy of teaching and learning. Although most CRE teachers are academically trained and have professional competencies, they encounter a number of challenges in the use of life approach in teaching the subject. The purpose of this study to identify the ways in which the various constraints facing teachers of CRE in the use of life approach can be adequately addressed
Keywords: Teaching; Education; Constraints; Learning